Manajemen Pengelolaan Samsara Living Museum Sebagai Daya Tarik Wisata Budaya Di Desa Jungutan, Kecamatan Bebandem, Kabupaten Karangasem - Ida Ayu Karina Putri; Komang Shintiya Nita Kristiana Putri (JURNAL DESTINASI PARIWISATA, 2022)
Karangasem Regency has a very varied topography such as plains, hills and mountains. Through the image ofthe destination "Karangasem, The Spirit of Bali", Karangasem Regency has a vision and mission to preserveand introduce the existence of authentic Balinese values. Strengthening the image of destinations inKarangasem Regency is carried out through the development of the Samsara Living Museum of Life becausethis museum is not limited to mere physical space but interprets the noble values of Balinese people such asrituals, traditions, culture, and local wisdom. This study uses a qualitative method. Data collection usesseveral methods such as interviews, observation and documentation. This research using key person as theinformant. The results show Samsara Living Museum puts forward activities related to the preservation ofBalinese art and culture. The implementation of management at the Samsara Living Museum consists ofpreserving cultural heritage assets, such as heirlooms, historical manuscripts and literacy, art and culturepackaging, building basic facilities, and building community business units.Keywords: Operation Management, Karangasem Regency and Samsara Living Museum